Method for preparing hydrocracking catalyst

By introducing rare earth ions and desalting treatment during the glue formation process of the hydrocracking catalyst, a core-shell structure phase catalyst with large pore volume and pore size is prepared, which solves the problem that existing catalysts are difficult to have high isomeristic properties and high aromatic conversion capabilities at the same time, and realizes a high-efficiency hydrocracking process suitable for special oils and lubricating oil base oils.

CN116943722BActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210403815.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-18
Publication Date
2025-05-02
Estimated Expiration
2042-04-18

AI Technical Summary

Technical Problem

The existing hydrocracking catalysts are difficult to have high isomeristic properties and high aromatic conversion capabilities at the same time. The low-priced sodium-containing raw materials used during the preparation process lead to high catalyst costs and large wastewater treatment costs, and the catalyst pore volume and pore size are small, making it difficult to form.

Method used

By introducing rare earth ions in a specific glue forming process and carrying out desalting treatment, a core-shell structure phase catalyst with a larger pore volume and pore size is prepared. The catalyst combines core-shell composite oxide particles and β molecular sieve to improve the hydrogenation and cracking properties of the catalyst.

Benefits of technology

It realizes the excellent isomer properties and high aromatic conversion capabilities of the catalyst. It is suitable for the hydrocracking process of producing special oils and lubricating oil base oils, meets the standard requirements of industrial-grade white oils and transformer oils, reduces operating costs and increases product added value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116943722B_ABST
    Figure CN116943722B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a hydrocracking catalyst, comprising: (1) adding a sodium aluminate solution, a sodium molybdate solution and CO2 gas into a Ni-containing solution A in parallel to form a gel, adding a surfactant during the reaction process, and obtaining slurry A after aging; (2) adding water and an oily liquid into a reactor, carrying out a gelling reaction on a Ni- and Al-containing solution B, a sodium tungstate solution, a basic precipitant and slurry A, adding an equal portion of a rare earth ion-containing solution each time when the pH value is constant after being lowered, and obtaining slurry B after aging; (3) filtering slurry B, forming it with β zeolite, and performing desalting treatment to obtain the catalyst. The method of the present invention introduces rare earth into the catalyst with a core-shell structure, and cooperates with a specific desalting treatment process to prepare a bulk catalyst with a larger pore volume and pore diameter and smaller active metal oxide particles. This catalyst has excellent isomerization performance and aromatic hydrocarbon conversion ability, and is suitable for the hydrocracking process for producing special oil and lubricating oil base oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum refining, and specifically relates to a preparation method of a hydrocracking catalyst and an application of the catalyst in a hydrocracking process for producing special oils. Background Art

[0002] Hydrocracking technology can directly convert various heavy and inferior feeds into petroleum products needed by the market. Hydrocracking diesel fractions have the characteristics of water white color, low impurity content, and high saturated hydrocarbon content. They can be blended to produce various white oils, rust-proof oils, transformer oils, aluminum cold rolling oils, etc. Compared with conventional hydrocracking products such as finished oil and chemical raw materials, transformer oil and industrial white oil have very strict requirements on low-temperature fluidity and aromatic content. Depending on the grade, the pour point index of industrial white oil is between -3~-9℃, and the aromatic content is required to be no more than 5%. Depending on the lowest cold state commissioning temperature in actual application, the pour point index range of transformer oil is between -10℃~-50℃, and the polycyclic aromatic hydrocarbon content is required to be less than 3%. Similarly, lubricating oil base oil also has corresponding requirements in terms of pour point, viscosity index (related to aromatics), etc. This requires hydrocracking catalysts to have both high isomerization performance and high aromatic conversion capacity. It is difficult for existing hydrocracking catalyst systems to take both into account.

[0003] The use of impregnation and kneading methods to prepare catalysts results in high catalyst preparation costs and large wastewater treatment costs because relatively low-priced sodium metal salt raw materials cannot be used. The coprecipitation method can use relatively low-priced sodium raw materials to prepare catalysts, which greatly reduces the catalyst preparation costs and wastewater treatment costs. However, the introduction of a large number of sodium ions makes it difficult to remove sodium ions from the catalyst. Even if the number of washings is increased (the increase in the number of washings will reduce the crushing strength of the catalyst), only the sodium ions on the surface of the catalyst can be removed. A large number of sodium ions still exist in the precipitated material. The residual sodium ions lead to poor adhesion of the material. The sodium ions that are not removed are not conducive to the formation of the catalyst pore structure, resulting in a small pore volume and pore size of the catalyst. At the same time, the existing co-precipitation preparation mostly uses ammonia water as a precipitant and nitrogen-containing soluble salts as raw materials. Although the physicochemical properties of the catalyst are improved by adopting different preparation methods and different acidic components to improve the hydrogenation activity and isomerization performance of the catalyst, it does not fundamentally solve the problems of smaller pore volume and specific surface area as the active metal increases in the bulk catalyst, smaller pore size of the catalyst (pore size distribution is mainly concentrated below 8nm), difficult molding, and larger metal oxide particles in the catalyst. At the same time, there are still problems such as poor dispersion of active metals, poor interaction between active metal components, and poor coordination between hydrogenation components and acidic components. It cannot have excellent isomerization performance and high aromatic conversion ability at the same time, and cannot meet the requirements of direct production of special oils by hydrocracking process.

[0004] CN1351124A discloses a medium oil type hydrocracking catalyst and its preparation and application. The catalyst is prepared by coprecipitation reaction, and the catalyst composition is amorphous silicon aluminum as the main carrier, the acidic component is modified Y zeolite, VIB group metal oxide accounts for 10% to 40%, VIII group metal oxide accounts for 1% to 20%, and IVB group metal accounts for 1% to 10%. When the catalyst treats vacuum distillate oil with high sulfur and nitrogen impurities, it has a high ability to resist nitride poisoning, high medium oil selectivity and high hydrocracking activity. The properties of the diesel fraction produced by hydrocracking by the catalyst prepared by this method cannot meet the standard requirements of industrial grade white oil, and can only be used as industrial grade white oil base oil. It must undergo deep dewaxing, hydrocracking and other process treatments to obtain industrial grade white oil products. Its production process is long, the operation is complicated and the investment cost is high.

[0005] CN102039151A discloses a hydrocracking catalyst and a preparation method thereof. The catalyst is prepared by a carbonization method and is amorphous silicon aluminum treated by hydrothermal treatment. The amorphous silicon aluminum obtained by the method has the characteristics of large specific surface, large pore volume, concentrated pore distribution and suitable acidity. The hydrogenation metal has high dispersibility, which improves the utilization rate of the metal and has high medium oil selectivity. However, the catalyst is a conventional catalyst with a low active metal content, and the pore distribution is mainly concentrated in 4 to 10 nm. The hydrogenation activity of the catalyst is insufficient, and the aromatic content in the obtained diesel fraction does not meet the standard of industrial-grade white oil products.

[0006] CN106513006A discloses a method for preparing a bulk hydrorefining catalyst, which comprises: pre-dispersing a Ni-containing compound with deionized water under an ultrasonic environment, then adding a Mo-containing compound to form a Ni-Mo fine grain structure, then adding a W-containing compound and a complexing agent to carry out a hydrothermal reaction, and then kneading and extruding the obtained active component powder with aluminum hydroxide dry glue, drying and calcining to obtain a catalyst. The catalyst prepared by the method of the present invention has uniform dispersion between different active phase grains, the W source is embedded in the Ni-Mo skeleton structure, the Ni-W active phase is easily wrapped by the Ni-Mo active phase at a microscopic level, and no oxide core-shell structure is obtained at a macroscopic level, the pore volume is small, the effective active phase is not much, the metal oxide particles are large, the hydrodenitrogenation activity is not improved, and the removal efficiency of nitrogen in macromolecular nitrogen-containing compounds is limited. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing a hydrocracking catalyst. The method of the present invention introduces rare earth into a core-shell structure catalyst in a specific gelling process and simultaneously performs a specific desalting process to prepare a core-shell structure bulk catalyst with large pore volume and pore diameter and small active metal oxide particles. The catalyst has excellent isomerization performance and aromatic conversion ability and is suitable for the hydrocracking process of producing specialty oils and lubricating oil base oils.

[0008] The preparation method of the hydrocracking catalyst of the present invention comprises the following contents:

[0009] (1) adding a sodium aluminate solution, a sodium molybdate solution and CO2 gas in parallel to a Ni-containing solution A to perform a gelling reaction, adding an anionic surfactant having a carbon number of C9 to C26 during the reaction, and aging after the reaction to obtain a slurry A;

[0010] (2) Dividing the rare earth ion solution into n equal parts by volume, adding water and oily liquid into the reactor, and then adding Ni and Al-containing solution B, sodium tungstate solution, alkaline precipitant aqueous solution and slurry A into the reactor in parallel to perform a stepwise pH reduction to form a gelation reaction, wherein the pH value is reduced from the initial value to the final pH value 2 to 10 times, preferably 2 to 8 times, and adding an equal part of the rare earth ion solution when the pH value is constant after each reduction. After the gelation reaction is completed, the slurry B is obtained after aging;

[0011] (3) filtering the slurry B, drying the filter cake, rolling and mixing it with the β molecular sieve, and forming a molded product;

[0012] (4) The formed product is desalted, washed, dried and calcined to obtain a hydrocracking catalyst.

[0013] In the method of the present invention, in the Ni-containing solution A described in step (1), the weight concentration of Ni in terms of NiO is 7 to 140 g / L, preferably 10 to 140 g / L; when preparing the Ni-containing solution A, the nickel source generally used is one or more of nickel sulfate, nickel nitrate, and nickel chloride.

[0014] In the method of the present invention, in the sodium molybdate solution in step (1), the weight concentration of Mo in terms of MoO3 is 8 to 150 g / L, preferably 10 to 145 g / L.

[0015] In the method of the present invention, the molar ratio of the total amount of CO2 gas added in step (1) to Al2O3 in the sodium aluminate solution is 1.0:1 to 5.0:1, and the concentration of CO2 gas is 20v% to 60v%;

[0016] In the method of the present invention, the concentration of the sodium aluminate solution in step (1) is 3-90 g / L, preferably 5-80 g / L, in terms of Al2O3 concentration.

[0017] In the method of the present invention, the C9-C26 anionic surfactant described in step (1) is selected from one or more of sulfonate type, carboxylate type, sulfate ester salt type, sulfate ester type, phosphate ester salt type, and phosphate ester type anionic surfactants, and is further selected from one or more of sodium lignin sulfonate, sodium alkyl glyceryl ether sulfonate, sodium dioctyl succinate sulfonate, sodium alkylbenzene sulfonate with carbon atoms of C10-C16, sodium oleic acid ethylene glycol diester sulfonate, sodium dibutylnaphthalene sulfonate, sodium dodecyl glyceryl ether carboxylate, sodium α-olefin sulfonate with carbon atoms of C14-C18, sodium lauryl alcohol polyoxyethylene ether sulfate, sodium monoglyceride disulfate, and the like.

[0018] In the method of the present invention, the molar ratio of the amount of the C9-C26 anionic surfactant added to the Mo in the sodium molybdate solution in step (1) is 0.2:1-2.0:1, preferably 0.3:1-1.8:1.

[0019] In the method of the present invention, the anionic surfactant in step (1) can be added along with the solution during the co-flow gelation process, or can be added when preparing solution A.

[0020] In the method of the present invention, the conditions for the gelling reaction in step (1) are: reaction temperature of 30-90°C, preferably 40-85°C, pH value of 7.0-11.0, preferably 7.2-10.0, and gelling time of 0.2-2.5 hours, preferably 0.3-2.0 hours.

[0021] In the method of the present invention, the aging conditions in step (1) are as follows: the aging temperature is 60-90°C, preferably 65-85°C, the pH value during aging is 7.0-11.0, preferably 7.2-10.5, and the aging time is 0.3-2.5 hours, preferably 0.5-2.0 hours.

[0022] In the method of the present invention, in step (1), the weight of the Ni introduced accounts for 20% to 80% of the total Ni weight in the hydrocracking catalyst obtained in step (4), preferably 25% to 78%.

[0023] In the method of the present invention, in the solution B described in step (2), the weight concentration of Ni calculated as NiO is 5-140 g / L, preferably 10-130 g / L, and the weight concentration of Al calculated as Al2O3 is 2-95 g / L, preferably 5-85 g / L.

[0024] In the method of the present invention, in the sodium tungstate solution described in step (2), the weight concentration of W calculated as WO3 is 6-150 g / L, preferably 8-140 g / L; when preparing the solution in step (2), the nickel source generally used is one or more of nickel sulfate, nickel nitrate, and nickel chloride, and the aluminum source is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, and aluminum acetate.

[0025] In the method of the present invention, the mass concentration of the solution containing rare earth ions in step (2) is 1-45 g / L, preferably 2-40 g / L, calculated as rare earth oxide. The rare earth is one or more of lanthanum, cerium, praseodymium and rubidium.

[0026] In the method of the present invention, the alkaline precipitant in step (2) is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, potassium carbonate, and potassium bicarbonate aqueous solution, preferably sodium carbonate and / or sodium hydroxide aqueous solution. The weight concentration of the alkaline precipitant aqueous solution can be 5% to 45%, and those skilled in the art can determine the amount according to actual needs.

[0027] In the method of the present invention, the water added in step (2) is deionized water, and the volume ratio of the added water to the volume of the slurry A obtained in step (1) is 0.1:1 to 3:1.

[0028] In the method of the present invention, the oily liquid in step (2) is unsaturated higher fatty acid glyceride (vegetable oil), preferably one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower oil, soybean oil, corn oil, tea oil, and olive oil. The volume ratio of the oily liquid to water is 1:60 to 1:4, preferably 1:40 to 1:6.

[0029] In the method of the present invention, the gelling reaction conditions described in step (2) are: the reaction temperature is 30-90°C, preferably 40-85°C, the initial pH value is 10.0-14.0, preferably 10.5-13.5, the final pH value is 7.0-8.5, preferably 7.2-8.3, and the gelling reaction time is 0.5-6.0 hours, preferably 0.6-5.0 hours. The stepwise downward adjustment method is to adjust the pH value to the desired value of the current time, and keep the pH value of the reaction slurry constant until the next downward adjustment begins, and the number of downward adjustments is 2-10 times, preferably 2-8 times. Preferably, it is preferably kept constant for 0.1-1.2 hours after each downward adjustment. The amplitude of each downward adjustment can be the same or different, and it is preferred that the amplitude of the pH reduction of the current downward adjustment is equal to or less than the amplitude of the pH reduction of the previous downward adjustment. The time used for each downward adjustment process is from the start of the current downward adjustment to the start of the next downward adjustment, and further, it is the sum of the time used for each pH downward adjustment and the time when the pH value is constant. The time used for each downward adjustment process can be the same or different, and preferably the time is the same.

[0030] In the method of the present invention, the aging conditions in step (2) are as follows: the aging temperature is 40 to 90° C., the aging time is 1 to 5 hours, and the pH value is 7.0 to 11.0.

[0031] In the method of the present invention, the aging conditions described in step (2) are preferably carried out as follows: the first step is normal pressure aging: the aging temperature is 30-90°C, preferably 40-80°C, the aging time is 1-6 hours, preferably 1.2-5 hours, and the pH value is 6.5-10.0, preferably 7.0-9.0; the second step is high pressure aging: the temperature is 100-195°C, preferably 100-190°C, the time is 0.1-3.5 hours, preferably 0.3-2.8 hours, the pressure is not less than 10 MPa, preferably 10-15 MPa, and the pH value is 10.0-13.0, preferably 10.0-12.5.

[0032] The mild conditions in the aging process of step (2) are more conducive to the formation of uniform particle size. During the aging process in a closed environment, the phase structure of the material has formed a regular body in the first step of aging. However, in a closed environment, under the action of high temperature and pressure, the microscopic morphology of the material changes, and the material phase changes from a regular body to an irregular body formed by irregular flakes. This structural change causes the sodium ions inside the phase to transfer to the surface of the phase, which is more conducive to the next step of desalination treatment. It is also conducive to increasing the specific surface area of ​​the bulk catalyst and improving the pore structure, so that more active metals are exposed on the catalyst surface, and more hydrogenation active centers are generated on the catalyst surface.

[0033] In the method of the present invention, the drying temperature in step (3) is 50 to 140° C., and the drying time is 0.5 to 24 hours.

[0034] In the method of the present invention, the rolling mixing and molding process described in step (3) is well known in the field of catalyst preparation. An extrusion aid and a peptizing agent are generally added during the extrusion molding process. The extrusion aid can be one or more of sesbania powder, carbon black, graphite powder or cellulose, and the peptizing agent is generally an acid solution containing one or more of hydrochloric acid, sulfuric acid, acetic acid, etc. The amount of the extrusion aid accounts for 1wt% to 10wt% of the total material dry basis. The catalyst of the present invention can be prepared into the shape of flakes, spheres, cylindrical strips and special-shaped strips (three-leaf clover, four-leaf clover) as needed.

[0035] In the method of the present invention, the beta molecular sieve described in step (3) has the following properties: a molar ratio of silicon oxide to aluminum oxide of 30 to 85; a specific surface area of ​​350 to 780 m 2 / g, preferably 450~700m 2 / g; pore volume is 0.30~0.80cm 3 / g, preferably 0.35~0.75cm 3 / g; the infrared acid content is 0.10~0.55mmol / g, preferably 0.18~0.50mmol / g.

[0036] In the method of the present invention, the β molecular sieve described in step (3) can also be added after the aging of the slurry B is completed.

[0037] In the method of the present invention, the desalination treatment process described in step (4) is: first curing, and then washing to remove the salt precipitated on the surface of the molded object, the curing conditions are a temperature of 5 to 100°C, preferably a temperature of 10 to 90°C, and a time of 10 to 100 hours, preferably 24 to 90 hours.

[0038] In the method of the present invention, the desalination treatment described in step (4) is preferably carried out in the following manner: in the first stage, the temperature is 60 to 90° C., and the curing time is 5 to 70 hours, preferably 8 to 65 hours, so that the hydrated sodium ions are precipitated and vacancies are retained; in the second stage, the temperature is 10 to 30° C., and the time is 1 to 48 hours, preferably 3 to 45 hours, so that the vacancies are retained and shrunk, so that the pore volume of the catalyst is increased and the catalyst has good mechanical strength, and then the precipitated salt is removed by washing.

[0039] In the method of the present invention, the washing, drying and roasting in step (4) can be carried out under conventional conditions in the art. The drying conditions are as follows: drying at 40-150°C for 1-48 hours, preferably drying at 50-120°C for 4-36 hours. The roasting conditions are as follows: roasting at 350-650°C for 1-24 hours, preferably roasting at 400-600°C for 2-12 hours. Washing is generally carried out with deionized water or ethanol solution until neutral.

[0040] In the method of the present invention, based on the weight of the hydrocracking catalyst obtained in step (4), the content of the β molecular sieve added in step (3) satisfies: the content of the β molecular sieve is 6% to 23%, preferably 7% to 20%.

[0041] The hydrocracking catalyst of the present invention comprises core-shell composite oxide particles and beta molecular sieves. Based on the weight of the hydrocracking catalyst, the content of the beta molecular sieve is 6% to 23%, preferably 7% to 20%; the content of the core-shell composite oxide particles is 77% to 94%, preferably 80% to 93%; in the core-shell composite oxide particles, the core phase is a composite oxide containing molybdenum, nickel and aluminum, the shell phase is a composite oxide containing tungsten, nickel, rare earth and aluminum, and the average particle size of the core-shell composite oxide particles is 9 to 14 nm; preferably, the particle size distribution of the core-shell composite oxide particles is as follows: the number of particles with a particle size less than 9 nm accounts for 3% to 14% of the total number of particles, the number of particles with a particle size of 9 nm to 14 nm accounts for 67% to 90% of the total number of particles, and the number of particles with a particle size greater than 14 nm accounts for 3% to 17% of the total number of particles.

[0042] In the hydrocracking catalyst of the present invention, the beta molecular sieve has the following properties: a molar ratio of silicon oxide to aluminum oxide of 30 to 85; a specific surface area of ​​350 to 780 m 2 / g, preferably 450~700m 2 / g; pore volume is 0.30~0.80cm 3 / g, preferably 0.35~0.75cm 3 / g; the infrared acid content is 0.10~0.55mmol / g, preferably 0.18~0.50mmol / g.

[0043] In the hydrocracking catalyst of the present invention, based on the mass of the core-shell structured composite oxide particles, the core phase accounts for 15% to 90%, preferably 18% to 85%, and the shell phase accounts for 10% to 85%, preferably 15% to 82%.

[0044] In the hydrocracking catalyst of the present invention, the molar ratio of molybdenum to nickel in the core phase is 1:25-12:1, preferably 1:22-10:1, and the content of aluminum in terms of Al2O3 accounts for 2%-15% of the mass of the hydrocracking catalyst, preferably 3%-13%.

[0045] In the hydrocracking catalyst of the present invention, the molar ratio of tungsten to nickel in the shell phase is 1:25~8:1, preferably 1:20~5:1, the content of aluminum is 2%~13% of the mass of the hydrocracking catalyst calculated as Al2O3, preferably 2%~11%, and the content of rare earth is 2%~12% of the mass of the hydrocracking catalyst calculated as rare earth metal oxide, preferably 3%~10%.

[0046] In the hydrocracking catalyst of the present invention, NiO in the core phase accounts for 20% to 80% of the total mass of NiO in the hydrocracking catalyst, and NiO in the shell phase accounts for 20% to 80% of the total mass of NiO in the hydrocracking catalyst.

[0047] In the hydrocracking catalyst of the present invention, the properties of the hydrocracking catalyst are as follows: the specific surface area is 200~750m 2 / g, and the pore volume is 0.20~0.90mL / g.

[0048] The hydrocracking catalyst of the present invention can be in the form of flakes, spheres, cylindrical bars and special-shaped bars (three-leaf clover, four-leaf clover) as required, preferably cylindrical bars and special-shaped bars (three-leaf clover, four-leaf clover).

[0049] The pore size distribution of the hydrocracking catalyst of the present invention is as follows: the pore volume occupied by pores with a diameter of less than 4 nm accounts for 1% to 9% of the total pore volume, the pore volume occupied by pores with a diameter of 4 to 10 nm accounts for 16% to 42% of the total pore volume, the pore volume occupied by pores with a diameter of 10 to 15 nm accounts for 30% to 56% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15 nm accounts for 17% to 42% of the total pore volume; the preferred pore size distribution is as follows: the pore volume occupied by pores with a diameter of less than 4 nm accounts for 2% to 8% of the total pore volume, the pore volume occupied by pores with a diameter of 4 to 10 nm accounts for 18% to 40% of the total pore volume, the pore volume occupied by pores with a diameter of 10 to 15 nm accounts for 32% to 54% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15 nm accounts for 20% to 40% of the total pore volume.

[0050] The hydrocracking catalyst of the present invention can be used in the hydrocracking process of the base oil for producing special oil and lubricating oil, and is particularly suitable for the hydrocracking process of the base oil raw material for producing transformer oil, white oil and high viscosity index lubricating oil. The catalyst of the present invention is used in the process of producing special oil by hydrocracking, and the aromatic content and pour point of the hydrocracking diesel fraction product can meet the requirements of the industrial-grade special oil base oil standard, and can reach the standard of the industrial-grade special oil base oil without further deep processing, thereby reducing the operating cost, increasing the added value of the product, and creating greater economic benefits.

[0051] Furthermore, the hydrocracking process adopts a one-stage series one-pass process.

[0052] Furthermore, the hydrocracking process uses vacuum distillate as a raw material to produce special oil and base oil for lubricating oil, wherein the special oil can be transformer oil or white oil.

[0053] Furthermore, the hydrocracking operating conditions are as follows: the reaction temperature is 320-500°C, preferably 340-450°C; the reaction pressure is 6-18 MPa, preferably 11-16 MPa; the liquid hourly volume space velocity is 0.4-3.0 h -1 , preferably 0.5~2.2 h -1 ; The volume ratio of hydrogen to oil is 300:1~2300:1, preferably 500:1~1800:1.

[0054] Compared with the prior art, the present invention has the following advantages:

[0055] 1. The hydrocracking catalyst of the present invention comprises core-shell composite oxide particles and β molecular sieve, wherein the core-shell composite oxide particles are composed of composite oxide particles containing molybdenum, nickel and aluminum coated with composite oxide containing tungsten, nickel, rare earth and aluminum. The coating structure is different from the structure at the macro level (such as millimeter level). The structure of the catalytic material is controlled at the micro level, and is coordinated with the acidic component (β molecular sieve) to promote good assistance between active metals and between active metals and acidic components, so that the overall performance of the catalyst is improved, the hydrogenation performance and cracking performance of the catalyst are improved, the catalyst has both high isomerization performance and high aromatic conversion ability, and the catalyst activity and selectivity are significantly improved.

[0056] 2. In the method of the present invention, molybdenum, nickel, and aluminum aged slurry are first prepared, and then added to the reaction tank containing water and greasy liquid in parallel with nickel and aluminum mixed solution, sodium tungstate solution, and precipitant for the second gelation, so that tungsten and nickel are uniformly and orderly precipitated on molybdenum and nickel grains, thereby forming tungsten-nickel coated molybdenum and nickel nanoparticles with uniform particle size and good dispersion, and β molecular sieve is introduced during molding, which matches well with β molecular sieve. At the same time, when preparing molybdenum, nickel, and aluminum aged slurry, CO2 gas is added to make the core phase metal dispersed evenly, so that the connecting channels between the core phase and the shell phase in the composite oxide particles are unobstructed, and further promote the cooperation between the active metal in the core phase and the acidic component. The method of the present invention also solves the problem that the catalyst prepared by the co-precipitation method is difficult to mold when the active metal content of the catalyst is large.

[0057] 3. The present invention uses relatively low-priced, clean raw materials (soluble sodium salts) to prepare catalysts. The active metal oxide materials after gelation contain a large amount of sodium ions. The inventors change the conventional thinking and retain the sodium salt in the materials during the molding process. The materials after molding are then subjected to a desalting process to remove the precipitated sodium salt. In this process, the vacancy of the sodium salt during the molding process is more conducive to the formation of the catalyst pore structure after sodium removal, and the pore distribution moves toward the macropore direction. The pore volume and pore size of the catalyst increase, and the probability of the active component carrier pore and the β molecular sieve pore interpenetration is increased. At the same time, the vacancies generated after sodium removal expose more active metals on the surface of the bulk catalyst, solving the problems encountered in the prior art in the process of increasing the metal content in the bulk catalyst, such as reduced catalyst pore volume, less active metal on the catalyst surface, and difficulty in molding. In the catalyst preparation process, the method of the present invention reduces the number of conventional catalyst preparation processes and reduces the amount of water. At the same time, the core-shell structure of the catalyst of the present invention further promotes the precipitation of sodium salts during the desalting process.

[0058] 4. In the method of the present invention, by adding a specific anionic surfactant in the gelling reaction of step (1), it is beneficial to control the growth of the core phase in the composite oxide particles, so that the average particle size of the composite oxide particles is reduced and the size is uniform. When the composite oxide of tungsten, nickel, rare earth and aluminum is formed in the gelling reaction of step (2), the pH value is gradually reduced to form a gel, so that the size of the core-shell composite oxide particles can be uniform. By adding rare earth metals when the pH value is constant after decreasing during the reaction process, the complex formed by the synergistic effect of rare earth and hydrogenation active metal has a high hydrogen storage capacity, increases the catalyst's absorption and dehydrogenation capacity, prevents the catalyst from carbonizing, and makes the catalyst have good activity stability. The core-shell composite oxide particles generated by the present invention are small, which is conducive to the better function of rare earth metals. In addition, by controlling the rare earth addition method, the rare earth metal is evenly distributed in the shell of the core-shell composite oxide particles, and the coordination effect of the rare earth metal and the active metal is enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a TEM photograph of catalyst B obtained in Example 2. DETAILED DESCRIPTION

[0060] In the present invention, the specific surface area and pore volume are measured by low temperature liquid nitrogen adsorption method, and the mechanical strength is measured by lateral pressure method. The specific surface area, pore volume and pore size distribution are measured by ASAP-2405 BET nitrogen adsorption instrument, and the crushing strength of the catalyst is measured by ZQJ-2 intelligent particle strength testing machine.

[0061] In the present invention, in the core-shell composite oxide particles, the metal content in the composite oxide in the core and the shell and the thickness of the shell are measured by TEM transmission electron microscope (Japan JSM-2100). Among them, the method for determining the metal content in the composite oxide in the core and the shell is as follows: the core-shell composite oxide particles are uniformly mixed with liquid epoxy resin, and then an appropriate amount of curing agent is added, and the mixture is heated and cured after being stirred evenly to form solid particles. The solid particles are cut into thin slices with a thickness of 5-20nm by an ultrathin slicer, and the obtained slices are placed in a transmission electron microscope for observation to find a core-shell structure (cross section) with a clear interface. The diameter of the electron beam is adjusted by a condenser so that its diameter basically covers the outline of the entire core-shell structure, and the energy spectrum EDS spectrum is collected to record the intensity of the main energy peak, which corresponds to the actual content of each element in the known feed and the energy peak intensity of each element. The electron beam diameter is adjusted so that it is smaller than or close to the core or shell size, and the metal content in the composite oxide in the core and the shell at this time is calculated according to the energy peak intensity corresponding to the element, compared with the peak intensity under full coverage and the corresponding actual value. In the core-shell structure, the shell thickness is identified and measured from the transmission electron microscope image, and the ratio of the shell thickness to the total core-shell thickness is the average value obtained by measuring 40 to 100 core-shell particles.

[0062] In the present invention, wt% refers to mass fraction, and v% refers to volume fraction.

[0063] In the present invention, the properties of the β molecular sieve used are shown in Table 7, and the properties of the Y molecular sieve are shown in Table 8.

[0064] Example 1

[0065] Add nickel chloride to a dissolution tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add nickel chloride and aluminum chloride solutions to a dissolution tank 2 filled with deionized water to prepare a solution B containing Ni and Al, wherein the weight concentration of Ni in the Ni-containing solution B is 28 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 8 g / L. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. Prepare a solution C containing rare earth ions (lanthanum) (the mass concentration of lanthanum in terms of oxide is 14 g / L), and divide it into 5 equal parts by volume. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 10 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L), a sodium lignin sulfonate solution and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, the molar ratio of the sodium lignin sulfonate to the Mo in the sodium molybdate solution is 1.1, the gelling temperature is maintained at 60°C, the pH value is controlled at 7.6 at the end of the reaction, the gelling time is controlled at 1.0 hour, and after the reaction is completed, aging is carried out at a temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. First, 1000mL of deionized water and 80mL of peanut oil were added to the reaction tank 2, and then the sodium carbonate solution with a concentration of 12wt%, the first slurry, the solution B containing Ni and Al, and the sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 for the second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times, and the final pH value at the end was adjusted to 7.8. The pH value of each adjustment was 1.0. After each adjustment to the adjusted value, it was kept constant. The adjusted pH value of the reaction slurry was kept constant for 12 minutes. During the constant process, an equal portion of the rare earth ion solution was added dropwise, and the dropping time was the same as the constant time. After the second gelation reaction was completed, aging began, the aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 80°C for 10 hours, and the dried material was mixed with the β molecular sieve and rolled to extrude into a clover shape. The formed strips were cured at 65°C for 52 hours, then the temperature was lowered to 25°C and cured for 30 hours. The strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain catalyst A. The catalyst composition and main properties are shown in Table 1.

[0066] Example 2

[0067] Add nickel chloride to a dissolving tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 54 g / L in terms of NiO. Then add nickel chloride and aluminum chloride solutions to a dissolving tank 2 filled with deionized water to prepare a solution B containing Ni and Al, wherein the weight concentration of Ni in the Ni-containing solution B is 20 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 8 g / L. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 27:10. Prepare a solution containing rare earth ions (lanthanum, cerium,) (the mass concentration of lanthanum, cerium, in terms of oxide is 12 g / L, based on the total weight of rare earth metal oxides, La2O3 accounts for 60.9%, and CeO2 accounts for 39.1%), and divide it into 6 equal parts by volume. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 18 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 48 g / L), sodium diisooctyl sulfonate succinate and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 3.8, the CO2 gas concentration is 57v%, the molar ratio of sodium diisooctyl sulfonate succinate to Mo in the sodium molybdate solution is 0.7, the gelling temperature is maintained at 60°C, the pH value is controlled at 8.4 at the end of the reaction, the gelling time is controlled at 1.7 hours, and after the reaction is completed, aging is carried out at a temperature of 78°C, the aging pH value is controlled at 8.4, and the aging is carried out for 1.7 hours to obtain a first slurry. First, 800 mL of deionized water and 80 mL of rapeseed oil were added to the reaction tank 2, and then a 12 wt % sodium hydroxide solution, the first slurry, a solution B containing Ni and Al, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 16 g / L) were added to the reaction tank 2 in parallel for a second gelling reaction. The gelling temperature was maintained at 55° C. The pH value was initially controlled to be 12.9. The pH value was lowered 6 times to adjust the final pH value to 7.5 at the end. The pH value was lowered by 0.9 each time. After each reduction to the adjusted value, it was kept constant. The adjusted pH value of the reaction slurry was kept constant for 10 minutes. During the constant process, an equal portion of the rare earth ion solution was added dropwise. The dropping time was the same as the constant time. After the second gelling reaction was completed, aging began. The aging temperature was 78° C., the pH value was controlled at 7.9, and the aging time was 3.2 hours to obtain a second slurry. The aged slurry was filtered, and the filter cake was dried at 80°C for 12 hours. The dried material was mixed with β molecular sieve and rolled, and extruded into clover-shaped strips. After curing the formed strips at 75°C for 45 hours, the temperature was reduced to 21°C and continued to cure for 33 hours. Washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 9.0 hours, and the dried material was calcined at 550°C for 4 hours to obtain catalyst B. The catalyst composition and main properties are shown in Table 1.

[0068] Example 3

[0069] Add nickel chloride to a dissolution tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 22 g / L in terms of NiO. Then add nickel chloride and aluminum chloride solutions to a dissolution tank 2 filled with deionized water to prepare a solution B containing Ni and Al, wherein the weight concentration of Ni in the Ni-containing solution B is 34 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 10 g / L. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 11:17. A solution containing rare earth ions (lanthanum, cerium, praseodymium, and rubidium) is prepared (the mass concentration of lanthanum, cerium, praseodymium, and rubidium as oxides is 14 g / L, based on the total weight of rare earth metal oxides, La2O3 accounts for 39.5%, CeO2 accounts for 25.3%, Pr2O5 accounts for 13.5%, and Nd2O3 accounts for 21.7%), and divided into 6 equal parts by volume. The Ni-containing solution A is placed in a reaction tank 1, and sodium aluminate solution (weight concentration of Al2O3 is 14 g / L), sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 40 g / L), sodium oleate glycol sulfonate and CO2 gas are added into the reaction tank 1 in parallel to carry out the first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 3.5, the CO2 gas concentration is 48v%, the molar ratio of sodium oleate glycol sulfonate to Mo in the sodium molybdate solution is 1.3, the gelling temperature is maintained at 55°C, the pH value is controlled at 8.6 at the end of the reaction, the gelling time is controlled at 1.0 hour, and after the reaction is completed, aging is carried out at a temperature of 77°C, the aging pH value is controlled at 8.4, and the aging is carried out for 1.8 hours to obtain the first slurry. First, 1000mL of deionized water and 90mL of tea oil were added to the reaction tank 2, and then a 10wt% sodium hydroxide solution, the first slurry, a solution B containing Ni and Al, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 in parallel for a second gelation reaction. The gelation temperature was maintained at 70°C, and the pH value was initially controlled to be 13.3. The pH value was lowered 6 times to adjust the final pH value to 7.3 at the end. The pH value was lowered by 1.0 each time, and the pH value was lowered to 7.3 each time. After the adjustment value, the pH value of the reaction slurry after adjustment is kept constant for 9 minutes. During the constant process, an equal portion of the rare earth ion solution is added dropwise, and the dropping time is the same as the constant time. After the second gelation reaction is completed, aging begins, the aging temperature is 77°C, the aging pH value is controlled at 8.2, and the aging is 2.5 hours. Then the precipitate slurry continues to be aged under high pressure, the pressure is 12.8MPa, the aging temperature is 175°C, the aging time is 1.2 hours, and the aging pH value is 11.2, and the second slurry is obtained. The aged slurry is filtered, and the filter cake is dried for the first time, dried at 90°C for 9 hours, and the dried material is mixed with the β molecular sieve and rolled, extruded into a clover shape, and cured at 50°C for 76 hours. Wash with deionized water at room temperature until neutral.The wet strips were then dried at 100°C for 10.0 hours, and the dried material was calcined at 510°C for 6 hours to obtain Catalyst C. The composition and main properties of the catalyst are shown in Table 1.

[0070] Example 4

[0071] Add nickel chloride to a dissolving tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 24 g / L in terms of NiO. Then add nickel chloride and aluminum chloride solutions to a dissolving tank 2 filled with deionized water to prepare a solution B containing Ni and Al, wherein the weight concentration of Ni in the Ni-containing solution B is 20 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 10 g / L. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 12:10. Prepare a solution containing rare earth ions (lanthanum, cerium, praseodymium), (the mass concentration of lanthanum, cerium, and praseodymium in terms of oxides is 12 g / L, based on the total weight of rare earth metal oxides, La2O3 accounts for 38.5%, CeO2 accounts for 36.3%, and Pr2O5 accounts for 25.2%), and divide it into 5 equal parts by volume. . The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 16 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 28 g / L), a sodium lauryl alcohol polyoxyethylene ether sulfate solution and CO2 gas are added in parallel to the reaction tank 1 for a first gelling reaction, the molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 4.5, the CO2 gas concentration is 50v%, the molar ratio of the sodium lauryl alcohol polyoxyethylene ether sulfate solution to the Mo in the sodium molybdate solution is 0.9, the gelling temperature is maintained at 65°C, the pH value is controlled at 7.8 at the end of the reaction, the gelling time is controlled at 0.9 hour, and after the reaction is completed, aging is carried out at a temperature of 76°C, an aging pH value is controlled at 8.3, and the aging is carried out for 1.9 hours to obtain a first slurry. First, 900 mL of deionized water and 700 mL of soybean oil were added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, the first slurry, a solution B containing Ni and Al, and a sodium tungstate solution (the weight concentration of W calculated as WO3 is 66 g / L) were added to the reaction tank 2 in parallel for the second gelation reaction. The gelation temperature was maintained at 65 °C, and the pH value was initially controlled to be 12.5. The pH value was adjusted down 5 times to adjust the final pH value to 8.0 at the end. The pH value was adjusted down by 0.9 each time, and the pH value was adjusted down to 8.0 each time. After the adjustment, the pH value of the reaction slurry is kept constant for 16 minutes. During the constant process, an equal portion of the rare earth ion solution is added dropwise, and the dropping time is the same as the constant time. After the second gelation reaction is completed, aging begins, the aging temperature is 79°C, the pH value is controlled at 8.3, and the aging time is 2.9 hours. Then the precipitate slurry continues to be aged under high pressure, the pressure is 13.1MPa, the aging temperature is 160°C, the aging time is 1.0 hour, and the aging pH value is 11.8 to obtain the second slurry. The aged slurry is filtered, the filter cake is dried at 70°C for 12 hours, the dried material is mixed with the β molecular sieve and rolled, and extruded into a clover shape. The formed strips are cured at a temperature of 75°C for 49 hours, the temperature is reduced to 14°C, and the curing is continued for 30 hours.The wet strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 120°C for 8.0 hours and the dried material was calcined at 530°C for 5 hours to obtain catalyst D. The catalyst composition and main properties are shown in Table 1.

[0072] Comparative Example 1

[0073] According to the catalyst active metal composition and preparation method of Example 1, the acidic component is Y molecular sieve, and the reference agent E is prepared. The specific process is as follows:

[0074] Add nickel chloride to a dissolution tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add nickel chloride and aluminum chloride solutions to a dissolution tank 2 filled with deionized water to prepare a solution B containing Ni and Al, wherein the weight concentration of Ni in the Ni-containing solution B is 28 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 8 g / L. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. Prepare a solution C containing rare earth ions (lanthanum) (the mass concentration of lanthanum in terms of oxide is 14 g / L), and divide it into 5 equal parts by volume. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 10 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L), a sodium lignin sulfonate solution and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, the molar ratio of the sodium lignin sulfonate to the Mo in the sodium molybdate solution is 1.1, the gelling temperature is maintained at 60°C, the pH value is controlled at 7.6 at the end of the reaction, the gelling time is controlled at 1.0 hour, and after the reaction is completed, aging is carried out at a temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. First, 1000mL of deionized water and 80mL of peanut oil were added to the reaction tank 2, and then the sodium carbonate solution with a concentration of 12wt%, the first slurry, the solution B containing Ni and Al, and the sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 for the second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times, and the final pH value at the end was adjusted to 7.8. The pH value was adjusted to 1.0 each time, and it was kept constant after each adjustment to the adjusted value. The adjusted pH value of the reaction slurry was kept constant for 12 minutes. During the constant process, one portion of the rare earth ion solution was added dropwise, and the dropping time was the same as the constant time. After the second gelation reaction was completed, aging began, the aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 80°C for 10 hours, and the dried material was mixed with the Y molecular sieve for rolling and extruded into a clover shape. The formed strips were cured at 65°C for 52 hours, then the temperature was lowered to 25°C and cured for 30 hours. The strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain Catalyst E. The composition and main properties of the catalyst are shown in Table 1.

[0075] Comparative Example 2

[0076] Reference agent F was prepared according to the preparation method of Example 1 (no grease was added to the gelling tank during the second step of gelling) and the catalyst composition.

[0077] Add nickel chloride to a dissolution tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add nickel chloride and aluminum chloride solutions to a dissolution tank 2 filled with deionized water to prepare a solution B containing Ni and Al, wherein the weight concentration of Ni in the Ni-containing solution B is 28 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 8 g / L. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. Prepare a solution C containing rare earth ions (lanthanum) (the mass concentration of lanthanum in terms of oxide is 14 g / L), and divide it into 5 equal parts by volume. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 10 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L), a sodium lignin sulfonate solution and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, the molar ratio of the sodium lignin sulfonate to the Mo in the sodium molybdate solution is 1.1, the gelling temperature is maintained at 60°C, the pH value is controlled at 7.6 at the end of the reaction, the gelling time is controlled at 1.0 hour, and after the reaction is completed, aging is carried out at a temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. First, 1000mL of deionized water was added to the reaction tank 2, and then a sodium carbonate solution with a concentration of 12wt%, the first slurry, a solution B containing Ni and Al, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 for the second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times, and the final pH value at the end was adjusted to 7.8. The pH value was adjusted to 1.0 each time, and it was kept constant after each adjustment to the adjusted value. The adjusted pH value of the reaction slurry was kept constant for 12 minutes. During the constant process, an equal portion of the rare earth ion solution was added dropwise, and the dropping time was the same as the constant time. After the second gelation reaction was completed, aging began, the aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 80°C for 10 hours, and the dried material was mixed with the β molecular sieve for rolling and extruded into a clover shape. The formed strips were cured at 65°C for 52 hours, then the temperature was lowered to 25°C and cured for 30 hours. The strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain Catalyst F. The composition and main properties of the catalyst are shown in Table 1.

[0078] Comparative Example 3

[0079] According to the method of Example 1, catalyst G was prepared according to the component content ratio of catalyst A in Table 1, and the formed strips were not subjected to desalination treatment.

[0080] Add nickel chloride to a dissolution tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add nickel chloride and aluminum chloride solutions to a dissolution tank 2 filled with deionized water to prepare a solution B containing Ni and Al, wherein the weight concentration of Ni in the Ni-containing solution B is 28 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 8 g / L. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. Prepare a solution C containing rare earth ions (lanthanum) (the mass concentration of lanthanum in terms of oxide is 14 g / L), and divide it into 5 equal parts by volume. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 10 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L), a sodium lignin sulfonate solution and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, the molar ratio of the sodium lignin sulfonate to the Mo in the sodium molybdate solution is 1.1, the gelling temperature is maintained at 60°C, the pH value is controlled at 7.6 at the end of the reaction, the gelling time is controlled at 1.0 hour, and after the reaction is completed, aging is carried out at a temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. First, 1000mL of deionized water and 80mL of peanut oil were added to the reaction tank 2, and then the sodium carbonate solution with a concentration of 12wt%, the first slurry, the solution B containing Ni and Al, and the sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 for the second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times, and the final pH value at the end was adjusted to 7.8. The pH value of each adjustment was 1.0. After each adjustment to the adjusted value, it was kept constant. The adjusted pH value of the reaction slurry was kept constant for 12 minutes. During the constant process, an equal portion of the rare earth ion solution was added dropwise, and the dropping time was the same as the constant time. After the second gelation reaction was completed, aging began, the aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 80°C for 10 hours, and the dried material was mixed with the β molecular sieve and rolled to extrude into a clover shape. The molded product was washed with deionized water at room temperature, but no molded product was obtained after washing. The powder was dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain catalyst G. The catalyst composition and main properties are shown in Table 1.

[0081] Comparative Example 4

[0082] According to the catalyst composition of Example 1, nickel chloride and aluminum chloride were dissolved in deionized water to prepare a mixed solution, wherein the weight concentration of Ni in terms of NiO was 68 g / L, and the weight concentration of Al in terms of Al2O3 was 32 g / L. 1000 mL of deionized water was added to a reaction tank, and a 10 wt% sodium hydroxide solution, a sodium molybdate solution (the weight concentration of Mo in terms of MoO3 was 32 g / L), a sodium tungstate solution (the weight concentration of W in terms of WO3 was 44 g / L) and the mixed solution were co-flowed in the reaction tank to form gel, the gelling temperature was maintained at 60°C, the pH value was controlled at 7.6 at the end of the reaction, and the gelling time was controlled at 1.0 hour to generate a precipitate slurry containing nickel, tungsten, molybdenum and aluminum. Then, the aging was carried out at an aging temperature of 80°C, the pH value was controlled at 7.8 during aging, and the aging was carried out for 2.5 hours. After filtration, deionized water was added to the filter cake, and after slurrying and mixing, the filter cake was filtered. The filter cake was dried at 80°C for 10 hours, mixed with β molecular sieve and rolled, extruded into strips, and the molded product was washed with deionized water at room temperature. No molded product was obtained after washing. The powder was dried in an oven at 100°C for 8 hours and calcined at 530°C for 4 hours to obtain the reference catalyst H. The catalyst composition and main properties are shown in Table 1.

[0083] Comparative Example 5

[0084] Reference agent I was prepared according to Example 1 of the method disclosed in CN103055927A, wherein the acidic component was β molecular sieve, and the specific steps were as follows:

[0085] Prepare acidic solution A: Prepare 240 ml of nickel chloride solution containing 150 g / l NiO and 1000 ml of ammonium metatungstate containing 80 g / l WO3, mix them in a 5-liter container, and dilute with 800 ml of deionized water. Prepare 600 ml of dilute water glass solution containing 70 g / l SiO2, and add it to the above mixed salt solution under stirring. Prepare alkaline sodium metaaluminate solution B: Prepare 1000 ml of alkaline solution containing 89 g / l Al2O3.

[0086] The temperature of mixed solution A was raised to 60°C, and part of solution B was added to mixed solution A. The pH value of the system was 9.0, and then CO2 gas was introduced until the pH value of the reaction system was 7.6. The above process was repeated 5 times;

[0087] After the gelation is completed, under continuous stirring, add β molecular sieve suspension, the properties of which are shown in Table 7, and evenly disperse it in the mixed slurry obtained by gelation, and age it at about 76°C for 2 hours. Filter, dry at 60°C for 6 hours, roll, extrude into strips, and wash with deionized water at room temperature. Then dry at 110°C for 10 hours and calcine at 530°C for 4 hours to obtain reference catalyst I, whose composition and main properties are shown in Table 1.

[0088] Comparative Example 6

[0089] According to the preparation method disclosed in CN106513006A, β molecular sieve was added to the obtained active component powder and mixed evenly to prepare reference agent J having a catalyst composition similar to that of Example 1 of the present invention. The specific process is as follows:

[0090] 25g of basic nickel carbonate and 300mL of deionized water were uniformly mixed and added to a 1L high-pressure ultrasonic reactor. The ultrasonic frequency was set to 60KHz, and the mixture was heated to 80°C. After being kept at this temperature for 1h, the ultrasonic frequency was reduced to 20KHz, the system temperature was increased to 120°C, 26.5g of ammonium molybdate and 3g of polyvinyl pyrrolidone were added, and then 10mL of 25wt% ammonia water was added dropwise to the system. After being kept at this temperature for 2h, the ultrasound was turned off, stirring was turned on, the speed was 300 rpm, 39.6g of ammonium metatungstate was added, and then citric acid was added until the pH of the system was 4.2. After being kept at this temperature for 2h, the heating was turned off, and the slurry was collected after the system was cooled to room temperature. The slurry was spray dried, and the inlet temperature and outlet temperature were controlled at about 200°C and 100°C, respectively. The obtained dry powder was roasted at 330°C in a muffle furnace for 3h to obtain the active component powder. β molecular sieve was added to the powder and mixed evenly. The active component powder, β molecular sieve mixture and aluminum hydroxide dry gel accounting for 40% of the weight of the active component powder were mixed, and then a 10% dilute nitric acid aqueous solution was added for kneading and extrusion to obtain strips with a diameter of 1.5 mm. The strips were dried at 110°C for 10 h and calcined at 400°C in a muffle furnace for 5 h to obtain reference agent J. The catalyst composition and main properties are shown in Table 1.

[0091] Example 5

[0092] This example is an activity evaluation experiment of the catalyst of the present invention, and is compared with the catalyst of the comparative example. The catalysts A, B, C of the present invention and the catalysts E, F, I, and J of the comparative examples (catalysts G and H did not obtain a molded product, and no activity evaluation experiment was performed) were used to conduct a comparative evaluation test on a 200mL small hydrogenation device. The evaluation conditions are: total reaction pressure 15.7MPa, hydrogen-oil volume ratio 1500:1, liquid hourly volume space velocity 1.5h -1 , reaction temperature 380℃, the raw material used for evaluation is Middle East vacuum wax oil, its main properties are shown in Table 4, and the evaluation results are shown in Table 5.

[0093] It can be seen from Table 1 that when the catalyst of the present invention uses a relatively high sodium-containing raw material in the preparation process, the catalyst has good crushing strength after desalting and washing after molding, while without desalting, the molded catalyst strips become powder after washing.

[0094] It can be seen from the process conditions and evaluation results of the catalyst activity evaluation that, compared with the comparative example catalyst, the catalyst of the present invention has both high isomerization performance and high aromatic saturation performance in the process of treating heavy raw material oil hydrocracking, and the properties such as the pour point and aromatic content of the diesel fraction can meet the standards of industrial-grade white oil and transformer oil, and can flexibly produce special oil products such as transformer oil, white oil and high viscosity index lubricating oil base oil raw materials, while the comparative example catalyst cannot have high isomerization performance and high aromatic saturation performance at the same time. At the same time, by comparing the evaluation results of Table 5 and Table 6, after long-term operation, the catalyst of the present invention still has high isomerization performance and high aromatic saturation performance, indicating that the catalyst has good stability.

[0095] Table 1 Composition and properties of catalysts prepared in Examples and Comparative Examples

[0096]

[0097] Table 1 Composition and properties of catalysts prepared in Examples and Comparative Examples

[0098]

[0099] Table 2 Composition of oxides in the core and shell of each catalyst core-shell particle (based on the mass of the catalyst)

[0100]

[0101] Table 3 Average particle size and particle size distribution of catalyst core-shell composite oxide particles

[0102]

[0103] Table 3 Average particle size and particle size distribution of catalyst core-shell composite oxide particles

[0104]

[0105] Table 4 Main properties of crude oil

[0106]

[0107] Table 5 Evaluation results of catalysts of Examples and Comparative Examples (operated for 200 hours)

[0108]

[0109] Table 6 Evaluation results of catalysts of Examples and Comparative Examples (operated for 2500 hours)

[0110]

[0111] Table 7 Properties of β molecular sieves in Examples and Comparative Examples

[0112]

[0113] Table 8 Properties of Y-type molecular sieves used in comparative examples of the present invention

[0114]

Claims

1. A method for preparing a hydrocracking catalyst, characterized in that The method comprises the following contents: (1) adding a sodium aluminate solution, a sodium molybdate solution and a CO2 gas to a solution A containing Ni in parallel to carry out a gelling reaction, adding an anionic surfactant having a carbon number of C9 to C26 during the reaction, and aging the solution after the reaction to obtain a slurry A; (2) dividing a solution containing rare earth ions into n equal parts by volume, adding water and an oily liquid into a reactor, and then adding a solution B containing Ni and Al, a sodium tungstate solution, an alkaline precipitant aqueous solution and a slurry A into a reactor in parallel to carry out a gelling reaction by gradually lowering the pH value, wherein the pH value is lowered from an initial value to a final pH value. The number of times is 2 to 10 times, and each time the pH value is adjusted downward and becomes constant, an equal portion of a rare earth ion solution is added. After the gelling reaction is completed, slurry B is obtained after aging; (3) the slurry B is filtered, and the filter cake is dried and then rolled and mixed with a β molecular sieve to form a molded product; (4) the molded product is desalted, washed, dried and calcined to obtain a hydrocracking catalyst; the oily liquid described in step (2) is an unsaturated higher fatty acid glyceride; the alkaline precipitant is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, potassium carbonate and potassium bicarbonate aqueous solution.

2. The method according to claim 1, characterized in that: In the Ni-containing solution A described in step (1), the weight concentration of Ni calculated as NiO is 7-140 g / L; in the sodium molybdate solution, the weight concentration of Mo calculated as MoO3 is 8-150 g / L; the molar ratio of the total amount of CO2 gas added to Al2O3 in the sodium aluminate solution is 1.0:1-5.0:1, and the concentration of CO2 gas is 20v%-60v%; the concentration of the sodium aluminate solution is 3-90 g / L in terms of Al2O3 concentration.

3. The method according to claim 1, characterized in that: The C9-C26 anionic surfactant described in step (1) is selected from one or more of sulfonate type, carboxylate type, sulfate ester type, sulfate ester type, phosphate ester type, and phosphate ester type anionic surfactants.

4. The method according to claim 1, characterized in that: The C9-C26 anionic surfactant described in step (1) is selected from one or more of sodium lignin sulfonate, sodium alkyl glyceryl ether sulfonate, sodium dioctyl succinate sulfonate, sodium alkyl benzene sulfonate with carbon atoms of C10-C16, sodium oleic acid ethylene glycol diester sulfonate, sodium dibutylnaphthalene sulfonate, sodium dodecyl glyceryl ether carboxylate, sodium α-olefin sulfonate with carbon atoms of C14-C18, sodium lauryl alcohol polyoxyethylene ether sulfate, and sodium monoglyceride disulfate.

5. The method according to claim 1, characterized in that: The molar ratio of the amount of the C9-C26 anionic surfactant added to the Mo in the sodium molybdate solution in step (1) is 0.2:1-2.0:

1.

6. The method according to claim 1, characterized in that: The gelling reaction conditions of step (1) are as follows: reaction temperature is 30-90°C, pH value is 7.0-11.0, and gelling time is 0.2-2.5 hours; the aging conditions are as follows: aging temperature is 60-90°C, pH value during aging is 7.0-11.0, and aging time is 0.3-2.5 hours.

7. The method according to claim 1, characterized in that: In step (1), the weight of the introduced Ni accounts for 20% to 80% of the total Ni weight in the hydrocracking catalyst obtained in step (4).

8. The method according to claim 1, characterized in that: In the solution B described in step (2), the weight concentration of Ni calculated as NiO is 5-140 g / L, and the weight concentration of Al calculated as Al2O3 is 2-95 g / L; in the sodium tungstate solution, the weight concentration of W calculated as WO3 is 6-150 g / L; and the weight concentration of the alkaline precipitant aqueous solution is 5%-45%.

9. The method according to claim 1, characterized in that: In step (2), the mass concentration of the solution containing rare earth ions is 1-45 g / L in terms of rare earth oxide; the rare earth is one or more of lanthanum, cerium, praseodymium and rubidium.

10. The method according to claim 1, characterized in that: The water added in step (2) is deionized water, and the volume ratio of the added water to the volume of the slurry A obtained in step (1) is 0.1:1 to 3:

1.

11. The method according to claim 1, characterized in that: The unsaturated higher fatty acid glyceride described in step (2) is one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower seed oil, soybean oil, corn oil, tea oil, and olive oil; the volume ratio of the unsaturated higher fatty acid glyceride to water is 1:60 to 1:

4.

12. The method according to claim 1, characterized in that: The gelling reaction conditions in step (2) are as follows: reaction temperature is 30-90°C, initial pH value is 10.0-14.0, final pH value is 7.0-8.5 at the end, and gelling reaction time is 0.5-6.0 hours.

13. The method according to claim 1, characterized in that: The aging conditions in step (2) are as follows: aging temperature is 40 to 90° C., aging time is 1 to 5 hours, and pH value is 7.0 to 11.

0.

14. The method according to claim 1, characterized in that: The aging conditions in step (2) are as follows: the first step is normal pressure aging: the aging temperature is 30-90°C, the aging time is 1-6 hours, and the pH value is 6.5-10.0; the second step is high pressure aging: the temperature is 100-195°C, the time is 0.1-3.5 hours, the pressure is 10-15 MPa, and the pH value is 10.0-13.

0.

15. The method according to claim 1, characterized in that: The beta molecular sieve described in step (3) has the following properties: a molar ratio of silicon oxide to aluminum oxide of 30 to 85; a specific surface area of ​​350 to 780 m 2 / g; pore volume is 0.30~0.80cm 3 / g; infrared acid content is 0.10~0.55mmol / g.

16. The method according to claim 1, characterized in that: The desalination process described in step (4) is: first curing, then washing to remove the salt precipitated on the surface of the molded product, the curing conditions are a temperature of 5 to 100° C. and a time of 10 to 100 hours.

17. The method according to claim 1, characterized in that: The desalination treatment in step (4) is carried out as follows: the first stage is carried out at a temperature of 60 to 90°C for curing for 5 to 70 hours; the second stage is carried out at a temperature of 10 to 30°C for 1 to 48 hours, and then the precipitated salt is removed by washing.

18. A hydrocracking catalyst prepared by the method according to any one of claims 1 to 17, characterized in that: The invention comprises core-shell composite oxide particles and beta molecular sieve, wherein the content of beta molecular sieve is 6% to 23% based on the weight of the hydrocracking catalyst; the content of the core-shell composite oxide particles is 77% to 94%; in the core-shell composite oxide particles, the core phase is a composite oxide containing molybdenum, nickel and aluminum, the shell phase is a composite oxide containing tungsten, nickel, rare earth and aluminum, and the average particle size of the core-shell composite oxide particles is 9 to 14 nm; based on the mass of the core-shell composite oxide particles, the core phase is 15% to 90%, and the shell phase is 10% to 85%; the molar ratio of molybdenum to nickel in the core phase is 1:25 to 12:1, and the content of aluminum in terms of Al2O3 accounts for 10% to 10% of the hydrocracking catalyst. The molar ratio of tungsten to nickel in the shell phase is 1:25~8:1, the content of aluminum in terms of Al2O3 accounts for 2%~13% of the mass of the hydrocracking catalyst, and the content of rare earth in terms of rare earth metal oxides accounts for 2%~12% of the mass of the hydrocracking catalyst; the pore size distribution of the hydrocracking catalyst is as follows: the pore volume occupied by pores with a diameter of less than 4nm accounts for 1%~9% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10nm accounts for 16%~42% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15nm accounts for 30%~56% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15nm accounts for 17%~42% of the total pore volume.

19. The catalyst according to claim 18, characterized in that: The pore size distribution of the hydrocracking catalyst is as follows: the pore volume occupied by pores with a diameter of less than 4 nm accounts for 2%~8% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10 nm accounts for 18%~40% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15 nm accounts for 32%~54% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15 nm accounts for 20%~40% of the total pore volume.

20. Use of a hydrocracking catalyst prepared by the method according to any one of claims 1 to 17 in a hydrocracking process for producing base oil raw materials for transformer oil, white oil and high viscosity index lubricating oil.

Citation Information

Patent Citations

  • Hydrocracking catalyst and preparation method thereof

    CN102039151A

  • Preparation method of hydrocracking catalyst

    CN103055927A

  • Preparation method of bulk-phase hydrofining catalyst

    CN106513006A

  • Medium-oilness hydrocracking catalyst and its preparing process and application

    CN1351124A

  • Hydrocracking catalyst and production method thereof

    CN110038596A